Disputa del método en Economía: monismo vs. pluralismo - Sánchez-Bayón, Antonio; Arpi, Roberto; Sánchez-Bayón, Antonio; Arpi, Roberto (Corporación Universitaria Americana, 2024)
Introduction: Introduction: Critical review of PoliticalEconomy on the dispute of the method in Economics and the updating of its debate to review the state of economic knowledge and face its current challenges. This dispute starts from the previous one, related to the theoretical renunciation and the instrumental and applied excess of Economics with the Neoclassical Synthesis, moving away from reality and its changes with its modelizations, besides generating a studentuneasiness. Objective: To synthesize the development of the disputes of the method according to the Austrian School, to take Economics out of the sphere of Natural Sciences and Engineering, and its reductions to equilibrium models and mathematical excesses. Methodology: the theoretical and methodological frameworks of the Austrian School, shared with other heterodox approaches of foundations (Neoinstitutionalist), are used to contrast them with those borrowed from Natural Sciences and Engineering and assumed by the Neoclassical Synthesis, with the pretension of being more predictive than realistic. Results: the main problems of economic knowledge are systematized and how to correct them (scientifically and educationally) to move to the Economics of knowledge and complexity. Conclusions: the current dispute of the method not only allows recovering the foundations of Economics (via hermeneutic turn and Copernican revolution in science and its teaching), but also its reconnection with Social Sciences and the changingsocial reality. It also favors the transition to the Economics of knowledge and complexity, and the secular polemic of developmentalists vs. decresentists is evidenced.